Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Show that if $u(t)$ solves $\dot{u} = Au$, then $v(t) = u(-t)$, solves $\dot{v} = Bv$, where $B = -A$.

Similarly, show that if u(t) solves $\dot{u} = Au$, then $v(t) = u(2t)$ solves $\dot{v} = Bv$, where $B = 2A$.

I don't know how to formally prove this. It seems obvious because since the solution $v(t) = u(-t)$ is the same as $u(t)$ but it has a scalar which is negative and a scalar can be taken out of the solution and placed outside which follows that we have $-A$. The same goes with the second part of the question.

share|improve this question
add comment

2 Answers 2

up vote 2 down vote accepted

Let $s=-t$ then $dv(t)/dt=du(-t)/dt=-du(s)/ds=-Au(s)=-Au(-t)=-Av(t).$

Or let $s=kt$ with $k=-1,2$ then $dv(t)/dt=du(kt)/dt=(du(s)/ds)(ds/dt)=kAu(s)=kAu(kt)=kAv(t).$

share|improve this answer
add comment

Just substitute in to the differential equation and see that both sides are equal.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.